Land use decisions: By whom and to whose benefit? A serious game to uncover dynamics in farm land allocation at household level in northern Ghana - Michalscheck, Mirja; Groot, Jeroen C.J.; Fischer, Gundula; Tittonell, Pablo A. (Elsevier, 2020)
Globally, 38% of the land area is agricultural land, of which 45% are located on drylands, mainly in Africa and Asia, constituting the basis for about 60% of the world’s food production. Of all farms worldwide, 83% are smallholder farm systems, whose livelihoods depend on effective land management and allocation. While land is often cultivated by the various members of a farm household, land allocation decisions depend on the approval, the ambition and the abilities of influential household members, likely affecting all other household members, too. While intra-household decision-making processes have been described to depend on the interplay of prevailing interests and power positions, so far knowledge on interests and power positions is based on individual reports rather than actual observations. With the aim to explore the process of land allocation in a socially complex smallholder farm system, we invited members of a smallholder community in Northern Ghana to join a closed, experimental serious game, simulating a negotiation process between a male household head (HHH), a wife and the eldest son of a hypothetical local farm household. We observed an integrative negotiation style, resulting into high levels of satisfaction with the negotiation process and outcome by all parties, who reported a high level of similarity between simulated and real-life negotiations. Power was observed to be actively deployed, withheld or passively overruled depending on decision domains and process dynamics. While the HHH was the key decision maker acting as a strategic gatekeeper in a funnel-like process, the wife and the son had a significant influence on ‘his decision’ i.e. the household-level negotiation outcome. Model-based analysis also showed that the household-level outcome was more profitable as well as agro-biologically and nutritionally more diverse and productive as compared to the HHHs’ suggestion. The proposed game proved to be a culturally adequate, simple, cost and time-effective tool to capture how household-level land use decisions may come about and whose interests they represent. Our study provides a powerful framework for further research and for policies to foster more equitable land use decisions and therewith more sustainable socio-ecological systems.